EVALUATION AND IMPROVEMENT OF PERFORMANCE OF PROCUREMENT SUB-DEPARTMENT AT PT PAR - Fanny Gustaji, Rhamdalia
Business Process Management (BPM) is a management approach concentrated on improving corporate performance by managing a company’s business processes. BPM is a tool for operations to achieve good performance. Process improvement approach combined with statistical process control for measuring and limiting process variation and continuous improvement. One of the key performance indicators used is service time. Time delay on a particular project will impact a cost overrun. PT PAR, an oil and gas firm in Indonesia challenged to fulfill national energy targets of one million barrels/day. The company heavily relays on outsourced operational activities. Thus, the SCM department manages 60-80% of the company budget. In May 2022, the procurement sub-department in the SCM department faced decreasing their service time performance. This paper studies the evaluation of procurement sub-department service time performance using the Statistical Process Control method to know if there is any variation. Further, conduct a Capability Analysis to quantify the performance of a process. The results indicate the procurement process is under control. Nevertheless, it is not a capable process (CPK value >1.33) and is underperformance service time (PPM value >10%). The statistical result is the key for the SCM department to reengineer its procurement business process. The method used is Business Process Management and Business Process Reengineering. The author is mapping the business process in the SCM department for procurement or as-is design. Then, analyze the business process using Value Added Analysis. The results revealed several activities non-value-added and nonessential exist in the procurement process. The author proposed a business solution to reengineer the business process through the BPR method. The author modifies two activities increasing the success of the procurement process by 29% and lowering the maximum working days by 8.3%. The author recommends the new business process through activities: minimising the waste activity, aligning organisation structure, integrating software, and creating a new standard operating procedure.